Análise das entidades fechadas de previdência complementar sob a ótica da teoria da agência - Mano, Joaquim Chacur Biasotto (2022)
This paper analyzes the corporate governance of pension plan investment funds, to determine if their relevant corporate governance structures are efficient. This paper's theorical framework is agency theory, which discusses the problems caused by the separation of decision (control) and risk-bearing (ownership) functions. Pursuant to agency theory, ineffective governance structures result in agency problems which, at their most benign level, may result in poor investment decisions, but, at higher levels, can lead to serious losses to investors due to misconducts carried out by the management. To study this problem, this paper reviews Brazilian Law concerning governance of pension plan investment funds to assess whether it imposes an optimal governance structure to such funds, according to agency theory.